Interlanguage in the process of learning Brazilian Portuguese in tandem modality by using Hello Talk app - da Silva, Erika Suellem Castro (BELT - Brazilian English Language Teaching Journal, 2018)
Technology has been used for a variety of activities in our daily routine, including language learning. In that context, tandem modality has spread significantly (Telles; Vassalo, 2006; Souza, 2007; Telles; Ferreira, 2010). Basically, tandem requires two interactants to learn each other’s language in a collaborative way. Correction and feedback are essential elements in that modality. For this study, part of a project developed in a subject of the English Undergraduate Course at Pará State University (UEPA), we have pointed out the tandem learning in Hello Talk app of a German student learning Brazilian Portuguese by interacting with a Brazilian student learning English and German. We have observed specifically the interlanguage of the Brazilian Portuguese learner, regarding that errors are part of a complex process (Spinassé, 2006) of language acquisition, with its own systematicity, variability (Henriques, 2012) and specific levels.